Randomized Trial of C5a Receptor Inhibitor Avacopan in ANCA-Associated Vasculitis - Jayne, David R W; Bruchfeld, Annette N; Harper, Lorraine; Schaier, Matthias; Venning, Michael C; Hamilton, Patrick; Burst, Volker; Grundmann, Franziska; Jadoul, Michel; Szombati, István; Tesař, Vladimír; Segelmark, Mårten; et al. (Journal of the American Society of Nephrology, 2017)
Alternative C activation is involved in the pathogenesis of ANCA-associated vasculitis. However, glucocorticoids used as treatment contribute to the morbidity and mortality of vasculitis. We determined whether avacopan (CCX168), an orally administered, selective C5a receptor inhibitor, could replace oral glucocorticoids without compromising efficacy. In this randomized, placebo-controlled trial, adults with newly diagnosed or relapsing vasculitis received placebo plus prednisone starting at 60 mg daily (control group), avacopan (30 mg, twice daily) plus reduced-dose prednisone (20 mg daily), or avacopan (30 mg, twice daily) without prednisone. All patients received cyclophosphamide or rituximab. The primary efficacy measure was the proportion of patients achieving a ≥50% reduction in Birmingham Vasculitis Activity Score by week 12 and no worsening in any body system. We enrolled 67 patients, 23 in the control and 22 in each of the avacopan groups. Clinical response at week 12 was achieved in 14 of 20 (70.0%) control patients, 19 of 22 (86.4%) patients in the avacopan plus reduced-dose prednisone group (difference from control 16.4%; two-sided 90% confidence limit, -4.3% to 37.1%; P=0.002 for noninferiority), and 17 of 21 (81.0%) patients in the avacopan without prednisone group (difference from control 11.0%; two-sided 90% confidence limit, -11.0% to 32.9%; P=0.01 for noninferiority). Adverse events occurred in 21 of 23 (91%) control patients, 19 of 22 (86%) patients in the avacopan plus reduced-dose prednisone group, and 21 of 22 (96%) patients in the avacopan without prednisone group. In conclusion, C5a receptor inhibition with avacopan was effective in replacing high-dose glucocorticoids in treating vasculitis.
Keywords: senioři; dvojitá slepá metoda; Immunosuppressive Agents; complement 5a receptor; stupeň závažnosti nemoci; cyklofosfamid; Double-Blind Method; prednison; complement 5a; ANCA-associated vasculitis; Glucocorticoids; ANCA-asociované vaskulitidy; Drug Therapy, Combination; Middle Aged; receptor pro anafylatoxin C5a; mužské pohlaví; glukokortikoidy; Adult; aniliny; avacopan; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Rituximab; kombinovaná farmakoterapie; ženské pohlaví; Cyclophosphamide; imunosupresiva; Humans; ANCA; Aniline Compounds; Prednisone; Receptor, Anaphylatoxin C5a; rituximab; lidé středního věku; complement; Nipecotic Acids; kyseliny nipekotinové; dospělí; Female; Aged; Severity of Illness Index; lidé; Male